Effect of Post-Printing Conditions on the Mechanical and Optical Properties of 3D-Printed Dental Resin - Lassila, Lippo; Mangoush, Enas; He, Jingwei; Vallittu, Pekka K.; Garoushi, Sufyan (MPDI, 2025)
This study aimed to evaluate the flexural strength (FS), surface wear, and optical properties of 3D-printed dental resins subjected to different post-printing conditions. A total of 240 specimens (2 × 2 × 25 mm³) were 3D-printed using resin materials for permanent (VaresoSmile Crown Plus) VSC and temporary (VaresoSmile Temp) VST restorations. Specimens underwent five post-printing conditions: no post-printing cure; post-cured in a Form Cure curing unit; Visio Beta Vacuum; Ivoclar Targis; or heat-cured (150 °C) for 30 min. Each group of specimens (n = 24) was tested either directly after post-curing, after 24 h of dry storage, or following hydrothermal accelerated aging in boiling water for 16 h. The three-point bending test was used to evaluate the FS. The two-body wear test was performed on 50 disc-shaped specimens (n = 5/group). Surface gloss and translucency were measured for permanent VSC specimens (n = 5/group). SEM/EDS and statistical analyses were performed. The Form Cure device yielded the highest FS and lowest wear depth (p {\textless} 0.05). Hydrothermal aging significantly reduced FS. There were no statistical differences in FS and wear values between materials subjected to same post-printing conditions. VSC groups exhibited similar optical properties across different post-printing treatments. Post-printing treatment conditions had a significant impact on the FS and wear of the 3D-printed resin, while optical properties remained unaffected.